(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Antioxidant properties of the Piper cubeba plant’s leaves were chosen and studied. Utilizing a 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity, the antioxidant potential of the ethanol extract was investigated. The reduced color intensity was measured by using UV visible spectrophotometer at 517 nm. The ascorbic acid was used as a reference drug.